TASAWUF LOKAL DATU ABDUSSHAMAD BAKUMPAI DI MARABAHAN - Syadzali, Ahmad (Pascasarjana UIN ANTASARI Banjarmasin, 2013)
Syekh Datu Abdusshamad was a pioneer in spreading mystical Islam in Dayak?s land, especially among Bakumpais, indegenous people. Only by his significant role in this context, could Bakumpais take a part in the islamization procces of Dayaks. Their forgotten role in the history of local Islam must be caused by lackness of research conducted hitherto that mentioned sufficiently Bakumpais role with their distinctive character of religiosity and, even, Syekh Datu? Abdusshamad?s pioneership in that context